A Recent Progress of Spintronics Devices for Integrated Circuit Applications - Tetsuo Endoh; Hiroaki Honjo (Journal of Low Power Electronics and Applications, 2018)
Nonvolatile (NV) memory is a key element for future high-performance and low-power microelectronics. Among the proposed NV memories, spintronics-based ones are particularly attractive for applications, owing to their low-voltage and high-speed operation capability in addition to their high-endurance feature. There are three types of spintronics devices with different writing schemes: spin-transfer torque (STT), spin-orbit torque (SOT), and electric field (E-field) effect on magnetic anisotropy. The NV memories using STT have been studied and developed most actively and are about to enter into the market by major semiconductor foundry companies. On the other hand, a development of the NV memories using other writing schemes are now underway. In this review article, first, the recent advancement of the spintronics device using STT and the NV memories using them are reviewed. Next, spintronics devices using the other two writing schemes (SOT and E-field) are briefly reviewed, including issues to be addressed for the NV memories application.